Analysis of the Effect of Outreach on Cooperative Sustainability: The Mediating Role of Capital Deepening - Wahyudiono, Bambang; Tanjung, Hendri (AL-MUZARA'AH, 2025)
Indonesia is experiencing a serious inactivity of cooperatives, initially the number of active cooperatives was 209,448 units (2014) but has decreased to 130,119 units (2023) or a decrease of 79,328 units. This research aims to defined the effect of cooperative outreach on the sustainability of sharia saving and loan cooperatives (SLC). SLCs endeavor to elevate support provision to members. Mutually beneficial will be reached if financial and non-financial services (NFS) provided in a balanced manner. Utilizing data via questionnaires from 11 provinces in Indonesia or 32.3% of the total provinces, linear regression, mediation and moderation analysis were carried out. The analysis technique uses Structural Equation Model Partial Least Square (SEM PLS). The findings show a negative relationship between outreach and sustainability. Meanwhile, capital deepening has a positive effect and has a mediating effect on sustainability. However, NFS were found to have no moderating effect on this relationship. This research concludes that SLCs have to take a look at the capitals strength to maintain outreach, and should be wise regarding non-financial services. As a recommendation, the delivery of NFS needs a carefully consideration because apart from adding costs it also does not support the sustainability of the institution.